Smart packaging: overcoming barriers to medication adherence for older adults - Khayamian Esfahani, Bahar; Milisavljevic-Syed, Jelena; Lee, Kalok C. (AHFE International, 2024)
Medication adherence is essential for managing ageing illnesses due to the growing population of older adults who are increasingly multi-medicated. This paper explores the current challenges and future opportunities in enhancing medication adherence for older adults. It highlights the importance of leveraging home-based healthcare technologies for older adults based on their needs. There are various types of healthcare technologies and smart packaging options available in the market today. Some examples include smart pill and medication dispensers with smart packaging features, Mobile applications with reminders, manual pill boxes and organisers. These devices use features such as alarms, reminders, and tracking systems to help older adults with their routine. However, older adults' medication management can be affected by changing needs associated with ageing. As a result of ageing, their cognitive and physical abilities are rapidly changing due to various conditions including dementia, reduced vision, and decreased dexterity. Exploratory interviews were conducted with five older adults age 65 and over. The interviews focused on the participants' experiences with managing their medications, including challenges associated with rapidly changing medical conditions and capabilities. The major concern identified by participants was the complexity of managing multiple medications due to rapidly changing health conditions including forgetfulness, sensory impairments, neurological conditions, and reduced dexterity. The results have opened new avenues for future research in 1) smart packaging and design features that prioritises accessibility and ease of use, 2) leveraging Artificial Intelligence (AI) in smart packaging towards more personalised products to improve medication adherence in older adults.
Keywords: 46 Information and Computing Sciences; 4203 Health Services and Systems; 42 Health Sciences; Clinical Research; Behavioral and Social Science; Aging; 7.1 Individual care needs; Generic health relevance; Technologies; Healthcare; Medication adherence; Design thinking; Smart packaging